2012
DOI: 10.1590/s0103-64402012000400011
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro assessment of dentin erosion after immersion in acidic beverages: surface profile analysis and energy-dispersive X-ray fluorescence spectrometry study

Abstract: The aim of this study was to investigate the effects of some acidic drinks on dentin erosion, using methods of surface profile (SP) analysis and energy-dispersive X-ray fluorescence spectrometry (EDXRF). One hundred standardized dentin slabs obtained from bovine incisor roots were used. Dentin slabs measuring 5x5 mm were ground flat, polished and half of each specimen surface was protected with nail polish. For 60 min, the dentin surfaces were immersed in 50 mL of 5 different drinks (Gatorade®, Del Valle Mais … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
(21 reference statements)
2
26
0
1
Order By: Relevance
“…13 This frequent interaction compromises the properties of these materials, reflecting on esthetic damages and reduced duration. 6,7 Furthermore, the acidic environment promoted by acid food and beverages is correlated with dentin 14 and enamel 15 injury. Moreover, the degradation of restorative and prosthodontic materials has been also reported.…”
Section: Discussionmentioning
confidence: 99%
“…13 This frequent interaction compromises the properties of these materials, reflecting on esthetic damages and reduced duration. 6,7 Furthermore, the acidic environment promoted by acid food and beverages is correlated with dentin 14 and enamel 15 injury. Moreover, the degradation of restorative and prosthodontic materials has been also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several surveys observed the prevalence of erosion in children and adolescents in different locations around the world 14 . Only few studies have investigated the action, and the possible role, of ED in dental erosion [8][9][10][11] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other soft drinks, the majority of ED also have low pH and contain citric acid in its formulation 7 . Previous in vitro studies making use of profilometry and electron microscopy have demonstrated changes in the enamel and dentin caused by ED [8][9][10][11] . Decreased enamel hardness is the first sign of tooth erosion 12 , which is an important evidence of the action of erosive drinks in short exposures.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report to have applied nanoscratch testing to characterize early stages of enamel erosion from wine tasting. Our design is an improvement over previous in vitro models of wine erosion involving extensive periods of erosive demineralization, ranging from 1 hour to around 24 hours . Furthermore, nanoscratch testing also yields data on both enamel softening and surface roughness simultaneously, removing the need to conduct separate hardness testing and roughness measurements.…”
Section: Discussionmentioning
confidence: 99%